Controllable configuration of conductive pathway by tailoring the fiber alignment for ultrasensitive strain monitoring. (February 2021) - Yang, Jinzheng; Xu, Yanling; Song, Yangyang; Wang, Gongkai; Yin, Fuxing; Liu, Haitao; Yuan, Wenjing
Abstract: Fiber-based architectures exhibit remarkable advantages in wearable electronics. Despite the various techniques to achieve strain sensitive fibers, important factors concerning the sensing performance, e.g. fiber arrangement, have been rarely explored. Herein, various fiber sensing patterns with anisotropic and isotropic microstructures were fabricated, and their localized strain distribution and conductive pathway configuration were tailored through fiber alignment. The sensing performance and mechanisms were investigated based on experimental characterization and theoretical modeling. We find out that the fibers arrangement strongly determines their strain sensitive behavior including sensitivity and sensing range. Additionally, by introducing a mechanical-guided step to realize a constant microcrack density in the fiber patterns, strain sensitivity and stability can be further improved. As a proof of concept, we integrated two fiber array sensors into a strain sensing system to simultaneously achieve an ultrahigh sensitivity (gauge factor up to 9540) and a wide sensing range (0.01–110%) as well as fast response.